Modern methods of organic synthesis - Carruthers, William (Cambridge University Press, 2004)
Covering modern methods in organic synthesis, the fourth edition of this well-known textbook demonstrates their value, scope and use in the synthesis of complex molecules. All the text from the third edition has been completely re-written, making this an up-to-date account of current methods. A valuable textbook for students of chemistry and biochemistry at the graduate and senior undergraduate levels, the volume will also interest practicing scientists in industry and research establishments who wish to familiarize themselves with modern synthetic methods